Software para dispositivos móveis para diagnosticar superficies usinadas em madeira - Lima, Igor Ribeiro (2015)
The ASTM D 1666-87 1995 standard is responsible by qualification of woodwork machine surface. This qualification is subjective and is used by researches and furniture sector. The paper objective is to present a Mobile Specialist System that can aid in the diagnosis of wood work machine surface. In its implementation, fuzzy logic concepts were used in the representation and processing of knowledge base. Besides, programming language Java was used in its micro edition version. The percentage and intensity values of the defects are the entry variables in software. Java made possible greatest mobility toward software, concerning the usableness of the system in decision procedure of diagnosis of wood work machine surface. The preliminary results showed this software is able to give degrees for wood work machine surface, using the percentage and intensity values of the defects. This software could help the researches and furniture sector in the standardization of the degrees of the wood work machine surface, reducing the time and the costs of the machining process.